PENGARUH LOVE OF MONEY, RELIGIUSITAS, NILAI ETIS, TERHADAP KECENDERUNGAN KECURANGAN AKUNTANSI DAN IDEALISME SEBAGAI VARIABEL MODERATING (STUDI PADA MAHASISWA EKONOMI KOTA PALU) - Pakkawaru, Irham (Musawa: Journal for Gender Studies, 2020)
This research is the result of a verification study entitled “Effects of love of money, religiosity, and ethical values on the tendency of accounting fraud and idealism as a moderate variable in economics students in Palu. In this research, the researcher used quantitative research method. The data used were primary and secondary data. The research population were students majoring in Economics in Palu. The sampling technique was based on proportional random sampling. The researcher also used multiple regression analysis, different test and residual test. The results of this research showed that variable of love of money, religiosity, and ethical values had an effect on the tendency of accounting fraud, while idealism was not a moderating variable. In addition, there was an idealism difference between female and male students in Palu and there was no difference in the tendency between female and male students in Palu.